Restrictive Reciprocal Obligations: Perceptions of Parental Role in Career Choices of Sub-Saharan African Migrant Youths - Akosah-Twumasi, Peter; Emeto, Theophilus I.; Lindsay, Daniel; Tsey, Komla; Malau-Aduli, Bunmi S. (Frontiers in Psychology, 2021)
This study employed grounded theory methods and utilised semi‐structured interviews to explore how 31 African migrant high school and university students from eight sub-Saharan African representative countries and currently residing in Townsville, Australia perceived the roles of their parents in their career development. The study findings revealed that the support (financial, social, and emotional) and encouragement (sacrificial love, role modelling, and guidance) received from parents underpinned the youths’ perceptions of their parents as influential in their career trajectories. Though participants acknowledged their indebtedness to parents and the system that nurtured them, they faced a dilemma conforming to parental preference or personal conviction, which presented ‘a fork in the career decision-making road’. Study findings indicate that participants’ reactions and strategies for negotiating parental approval differ based on entry status and gender. Most participants, particularly those with professional entry status conformed to their parents’ career choice for fear of failure while a few who followed their personal interests negotiated parental approval through dialogue and educating parents. Majority of the male participants with humanitarian entry status opposed their parents’ career preferences and followed their own personal interests. Taken together, all participants had strong desire to obtain parental approval and whether sought early or later, the main focus for all participants was prioritising family needs and obligations. The practical implications of these findings for all stakeholders are discussed.